THE QIROATI METOD:AN EFFECTIVE APPROACH TO STRENGTHEN QUR'ANIC LITERACY IN ISLAMICELEMENTARY - nur faizah (Innovative Pedagogy and Education Studies, 2024)
This study explores the effectiveness of the Qiroati Method as an instructional approach to strengthening Qur’anic literacy in Islamic elementary schools. Qur’anic literacy is a fundamental aspect of Islamic education, encompassing students’ ability to read the Qur’an correctly in accordance with tajwid rules, fluency, and accuracy. The Qiroati Method emphasizes systematic learning, direct practice, and continuous evaluation, enabling students to develop strong foundational skills in Qur’anic reading from an early age. This research employs a qualitative descriptive approach, with data collected through classroom observations, interviews with teachers, and analysis of learning documents. The findings indicate that the implementation of the Qiroati Method significantly improves students’ reading accuracy, fluency, and confidence in reading the Qur’an. Additionally, the method encourages active student participation and disciplined learning habits. Despite challenges such as varying student abilities and limited instructional time, the Qiroati Method proves to be an effective approach to enhancing Qur’anic literacy in Islamic elementary education.